Changing Patterns of Sustainable Food Consumption Regarding Environmental and Social Impact-Insights From Slovakia - Holotová, Mária; Horská, Elena; Nagyová, Ĺudmila (Frontiers in Sustainable Food Systems, 2021)
Food consumption accounts for almost one-third of households' total environmental impact. Nowadays, consumption patterns throughout Europe are totally different from those of couple years ago, Slovakia is no exception. At an individual level, people's consumption patterns are shaped by their needs, abilities and opportunities. Exploring and understanding consumers' attitudes toward sustainable food consumption tendences is a key element to a better future for every country. This paper presents an analysis of the current situation regarding sustainable food habits among Slovak consumers. The main aim is to determine the level of consumer awareness for sustainable food consumption and food waste through purchasing decisions. Marketing research was conducted as a part of European project in five partner countries, we present results for Slovakia. Based on the analysis, we will be able in future to define limitations and opportunities in the form of recommendations in future. The findings of this paper have significant contributions and may encourage the process for the discussions and to provide the basis for educational content to help adults develop their skills and behaviors to make food consumption more sustainable.